Design and Testing Poultry Mixer Feed with Elbow Agitator - Simanjuntak, Melvin Emil; Lumbantoruan, Henry Hasian; Sitorus, Melvin B. H.; Simanjuntak, Janter P (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Currently, ruminant livestock, poultry and fish are increasingly using processed feed. It occurs due to the nutritional content can be adjusted to the needs. A lot of livestock will require a lot of feed, so a tool is needed that can mass produce the required feed. This processed feed is a mixture of several components that can be purchased individually. A motorized mixer is needed to save time and energy while reducing costs. The existing mixer has several shortcomings, such as the absence of a water supply device, a mixture that cannot be poured and a mixing spoon in the form of a flat plate so that the splint is less strong and the mixing process tends to be longer. The resulting prototype has a water supply pump, a pourable mixture, and an elbow-shaped agitator. Observations of the experimental results showed that the agitator material could move more toward the end so that the mixing process was faster. The mixed material became homogeneous in 5 minutes and perfect in the 10th minute for all experiments conducted.